Assessment of Undergraduates Civic Education Knowledge and Electoral Participation in Southwest Nigeria - Olugbenga Ajadi; Chinedu I. Okeke (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
The study investigated undergraduates’ civic education knowledge and electoral participation in Southwest Nigeria. It also investigated the relationship between undergraduate civic education knowledge and electoral participation. The study adopted convergent parallel mixed method with population of all undergraduates for all the public universities situated in the southwest, Nigeria. A sample of 600 respondents was selected using multistage sampling for the quantitative instrument, while 18 participants were purposively selected for qualitative instrument using focus group discussions. Data were collected using the Undergraduates’ Civic Education Knowledge and Electoral Participation Questionnaire (UCKEPQ) and a semi-structured interview guide for the focus group discussion. The questionnaire was validated and yielded a Cronbach’s alpha reliability of 0.82. Quantitative data were analyzed using descriptive statistics, Pearson Product Moment Correlation, and regression analysis at 0.05 significance level, while qualitative data were thematically analyzed. Results showed that undergraduates possessed moderate to high civic knowledge but exhibited low to moderate electoral participation. A significant positive relationship existed between civic knowledge and electoral participation (r = 0.67, p < 0.05). Civic education knowledge significantly influenced electoral participation (F = 136.84, p < 0.05), explaining 17.5% of the variance. Qualitative findings showed that political mistrust, insecurity, and weak youth mobilization hindered participation despite adequate civic education awareness. The study concludes that civic education knowledge alone does not ensure active electoral participation. It recommends experiential civic learning and reforms that strengthen trust in electoral institutions.